2022
DOI: 10.3390/antibiotics11040518
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Green Tea Polyphenol (−)-Epigallocatechin-3-Gallate (EGCG) against Clinical Isolates of Multidrug-Resistant Vibrio cholerae

Abstract: The spread of multidrug-resistant (MDR) Vibrio cholerae necessitates the development of novel prevention and treatment strategies. This study aims to evaluate the in vitro antibacterial activity of green tea polyphenol (−)-epigallocatechin-3-gallate (EGCG) against MDR V. cholerae. First, MIC and MBC values were evaluated by broth microdilution techniques against 45 V. cholerae strains. The checkerboard assay was then used to determine the synergistic effect of EGCG and tetracycline. The pharmaceutical mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Scanning electron microscopy (SEM) suggests that the physiological mechanism of action of EGCG may be related to membranes disrupting permeability. This is the first proof that EGCG works as a practical anti‐MDR V. cholerae medication [123] …”
Section: Antibacterial Activitymentioning
confidence: 66%
“…Scanning electron microscopy (SEM) suggests that the physiological mechanism of action of EGCG may be related to membranes disrupting permeability. This is the first proof that EGCG works as a practical anti‐MDR V. cholerae medication [123] …”
Section: Antibacterial Activitymentioning
confidence: 66%
“…Furthermore, OEO has been found to inhibit the tricarboxylic acid cycle pathway and its key enzymes, leading to effects on metabolites (Cui et al ., 2019). Studies have reported that the bactericidal effects of TP are mainly achieved through physical and chemical interactions of their chemical components with microbial cells (Sun et al ., 2021; Siriphap et al ., 2022). The main chemical components contained in TP are tannins, flavonoids and aromatic compounds, which can disrupt microbial cell membranes and cell walls, leading to the leakage of microbial cell contents and ultimately cell death (Yang & Zhang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The green tea catechins also manifest widerange of antibacterial activity through different mechanisms. 31 Specifically, this antibacterial property is due to the presence of phenolic compounds and flavonoids which are hydroxylated phenolic substances known to be produced by plants as a protective mechanism against microbial infection, and they have been determined to have antimicrobial substances against a broad array of microorganisms in vitro. 32 In this present study, all of the wild tea plants have the potential antiquorum sensing property through the prevention of the formation of biofilm of the different bacterial species.…”
Section: Discussionmentioning
confidence: 99%